COMORBIDITIES AND DEATHS BY COVID-19 IN BRAZIL - Souza, Izabella Ventura de; Scodro, Regiane Bertin de Lima; Dias Siqueira, Vera Lúcia; Fressatti Cardoso, Rosilene; Caleffi-Ferracioli, Katiany Rizzieri (Revista Uningá, 2021)
The new coronavirus outbreak in November 2019 quickly became an international public health emergency. Some studies demonstrate that the poor prognosis of the disease is directly related to the presence of comorbidities, with a risk of death increased by 3.4 times. Thus, the present study aimed to describe the cases of patients with Covid-19 that progressed to death in Brazil, evidencing age, sex, and presence of comorbidities. A retrospective, descriptive study was carried out with secondary data from patients with Covid-19 who progressed to death in Brazil, available on the websites of the health departments of each of the 27 federative units that make up the country. Data were tabulated and frequencies calculated in Microsoft Office Excel® 2007. There were 13,900,091 confirmed cases of Covid-19 until the 59th National Epidemiological Bulletin of 2021, of which 371,678 evolved to death; of them, 61.3% had comorbidities. Among the main comorbidities reported, heart disease (40.1%), diabetes (28.4%), obesity (10.3%), neurological diseases (5.0%), kidney diseases (4.7%) and pneumopathies (4.5%) stand out. In 70% of the cases of patients who died, age equal to or greater than 60 years was observed in males in 55% of the cases. The data obtained corroborate the literature, which indicate a poor prognosis of Covid-19 in patients with one or more comorbidities. Among these, the one that stood out in Brazil during the study period was heart disease.